Aren't we all exhausted already? EU copyright exhaustion and video game resales in the Games-as-a-Service era. (December 2020) - Trapova, Alina; Fava, Emanuele
Abstract : This article examines the issue of copyright exhaustion for digitally distributed video games in the EU. In light of the case law of the CJEU and national courts, it applies to video games two relevant dichotomies – sale/licence and goods/services. Diving into the modern Games-as-a-Service (GaaS) trend, it argues that treating all transactions as sales and all games as goods poorly reflects the complexity of today's video game industry. The many uncertainties of the current legal framework and the impractical consequences of digital exhaustion could force the industry to change its distribution models in ways not necessarily beneficial to consumers. Thus, the applicability of exhaustion to digitally distributed games should be ruled out once and for all. Nonetheless, where copyright is unable to offer satisfactory solutions, consumer law may protect players vis-à-vis digital distribution platforms, while at the same time providing legal certainty to the industry.